Adapting Communicative Language Teaching Approach to Enhance University Students’ English-Speaking Skills: A Qualitative Case Study in Timor-Leste - Zelia Maria da Costa; Magno Ximenes, Salvador (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This qualitative case study examines how the Communicative Language Teaching (CLT) approach can be adapted to general English classes in a higher education institution in Timor-Leste to answer the long-standing question of how students can acquire speaking proficiency in a multilingual learning environment. The paper brings into focus the incorporation of CLT into classroom activities with special emphasis on the application of role play, pair work, seminars, simulations, and task-based learning as means of promoting interactive and communicative competence. A descriptive qualitative case study design was used to develop in-depth knowledge of contextual teaching and learning experiences, the perspectives of the participants, and naturally occurring practices in the institutional setting. Semi-structured interviews, classroom observations, and document analysis were the data-gathering methods. Purposive sampling was used to select the two lecturers and seven students directly involved in teaching general English. Thematic analysis was used to analyse the data, which made it possible to identify repeated themes and patterns that revealed both opportunities and difficulties in implementing CLT in context. The results of the study indicate that, despite the adaptation of the CTL approach in teaching practices, its implementation is often sporadic due to concerns about English proficiency, teacher training, and flexibility in using local and official languages during instruction. The research demonstrates the necessity of adapting CLT methods to the local education environment and arranging long-term professional development for lecturers. This study helps us understand how context-sensitive CLT approaches can lead to improved results in teaching and learning English in Timor-Leste. The interactive approach and the systematic teacher model could significantly improve students' communicative competence.